Method for design and implementation of telecommunication devices for aircraft - Yerzhan, Assel; Kozhabayeva, Indira; Manbetova, Zhanat; Boykachev, Pavel; Nauryz, Kanysh; Zhazykbaeva, Zhazira; Seitova, Zhadra; Aitzhanova, Nursulu (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This article highlights the importance of electrical filters in radio engineering devices, emphasizing their role in transmitting signals in the transparency band and suppressing signals in the stop band. We examined methods for designing frequency-selective circuits with lumped parameters, which, in general, are a complete field of radio engineering and allow the synthesis of devices of varying complexity. The focus of the article is the frequency region, where the distributed properties of the synthesized structures appear. The article also provides an overview of various methods for synthesizing ultra-high frequency (UHF) filters. It is emphasized that for low-pass filters a transition from a low-frequency prototype to a high-frequency representation is applied, which, despite the crudeness of the approach, provides satisfactory results that can be improved at the production stage. The article also discusses various methods for implementing bandpass filters on distributed elements, including the use of short-circuited and open-circuited stubs, as well as weak-coupled lines. In conclusion, the paper highlights the need to improve these methods to improve process accuracy and make filter designers more efficient in radio engineering.